Étude Ethnobotanique et Screening Phytochimique de Quelques Ptéridophytes de la Forêt Classée de Yapo-Abbé (Côte d’Ivoire) - Dominique, Adou Lydie Marie; Jean-Marc, Zaouri Bi Gala; Kouadio, Bene; Noël, Zirihi Guédé (European Scientific Journal, ESJ, 2018)
An ethnobotanical study with phytochemical screening of some Pteridophytes was carried out in the classified forest of Yapo-Abbé in the south of Côte d’Ivoire, in the Agboville Department, precisely in the subprefecture of Azaguié. The objective of this study was to show the different uses of the Pteridophytes of this forest. The approach method is an ethnobotanical survey carried out among the populations of the study area. This survey consisted in drafting a questionnaire beforehand to apprehend the multiple uses of Pteridophytes among the surrounding population and to develop a photo album of Pteridophytes to be presented during the interview. The data collection was carried out using the semi-structured interview method and with the help of an interpreter guide. It identified 19 species of Pteridophytes including six (6) species used as medicinal plants. No other use of these taxa was mentioned. The whole plant is the most solicited or 73.33% for the preparation of medicinal recipes. Various methods of preparation such as decoction (33.3%), kneading (33.3%), softening (20%) and use in the fresh state (13.3%) are used for recipes. single species. There are also different modes of administration of phytomedicaments: drink (42.85%), local application (37.71%), mastication (7.14%) and massage (7.14%). The phytochemical sorting performed on the hydroethanolic extracts revealed that the different drugs of these plants contain sterols, polyterpenes, polyphenols, European Scientific Journal November 2018 edition Vol.14, No.33 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 174 flavonoids, catechin tannins, alkaloids and quinones which give them various therapeutic properties.